2008
DOI: 10.2106/jbjs.f.00847
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Retrieval Analysis of Clinically Failed Porous Tantalum Osteonecrosis Implants

Abstract: The retrieved implants were associated with little bone ingrowth and insufficient mechanical support of subchondral bone. The implant design, the surgical technique, its application, and the clinical characteristics of candidates for this procedure should continue to be monitored closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 8 publications
3
75
1
Order By: Relevance
“…Our findings showed, nevertheless, that two out of seven cases showed bony and vascular ingrowth, respectively, into the pores of the tantalum implant. Findings with a maximum bony ingrowth of 2.6 mm in a retrieved case after 12 months in situ are in accordance with the findings of Tanzer et al [22] and Fernández-Fairen et al [23] for porous tantalum osteonecrosis implants. Four rerevised cases showed a total lack of bony or vascular ingrowth although all tantalum augmentations were explanted with caution.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings showed, nevertheless, that two out of seven cases showed bony and vascular ingrowth, respectively, into the pores of the tantalum implant. Findings with a maximum bony ingrowth of 2.6 mm in a retrieved case after 12 months in situ are in accordance with the findings of Tanzer et al [22] and Fernández-Fairen et al [23] for porous tantalum osteonecrosis implants. Four rerevised cases showed a total lack of bony or vascular ingrowth although all tantalum augmentations were explanted with caution.…”
Section: Discussionsupporting
confidence: 90%
“…Tanzer et al [22] performed a histopathological retrieval analysis of 15 clinically failed specimens in 2008. Using backscattered scanning electron microscopy Tanzer et al confirmed the presence of bone ingrowth in 13 of the 15 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the simple insertion of the porous tantalum rod had a significant failure rate. Tanzer et al (2008) also reported 17 cases of tantalum rod failure, and suggested that single tantalum rod in the necrotic zone may be limited to conduct the formation of new bone and have a limited support to subchondral bone.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 In a recent study, 17 porous tantalum implants that were retrieved at the time of conversion to total hip arthroplasty were histopathologically analyzed. 50 All of them had been used for the management of stage II osteonecrosis of the femoral head according to Steinberg classification system. Osteonecrotic lesions were present in 14 of the 15 specimens (93%) that had been transected in situ near the base of the femoral head.…”
Section: Free Vascularized Fibula Graft Versus Porous Tantalum Implantmentioning
confidence: 99%